Covalent Triazine Frameworks (CTFs): Synthesis, Crystallization, and Photocatalytic Water Splitting. Issue 17 (6th February 2023) - Sun, Ruixue; Tan, Bien
Abstract: Covalent Triazine Frameworks (CTFs) have received great attention from academia owing to their unique structure characteristics such as nitrogen‐rich structure, chemical stability, fully conjugated skeleton and high surface area; all these unique properties make CTFs attractive for widespread applications, especially for photocatalytic applications. In this review, we aim to provide recent advances in the CTFs preparation, and mainly focus on their photocatalytic applications. This review provides a comprehensive and systematic overview of the CTFs' synthetic methods, crystallinity lifting strategies, and their applications for photocatalytic water splitting. Firstly, a brief background including the photocatalytic water splitting and crystallinity are provided. Then, synthetic methods related to CTFs and the strategies for enhancing the crystallinity are summarized and compared. After that, the general photocatalytic mechanism and the strategies to improve the photocatalytic performance of CTFs are discussed. Finally, the perspectives and challenges of fabricating high crystalline CTFs and designing CTFs with excellent photocatalytic performance are discussed, inspiring the development of CTF materials in photocatalytic applications. Abstract : Covalent Triazine Frameworks have received great attention as an attractive photocatalyst owing to their unique structure characteristics. This review provides a comprehensive overview of the CTFs' synthetic methods, crystallization, and applications for photocatalytic water splitting. The perspectives and challenges of fabricating high crystalline CTFs and designing CTFs with excellent photocatalytic performance are also discussed.